Medicinal plants used as anthelmintics: Ethnomedical, pharmacological, and phytochemical studies - Bailon Moscoso, N. (2017)
Intestinal parasites delay mental and physical development in children. Infection with these parasites can result in complications during pregnancy and alter the health of newborns, which has long-term effects on educational attainment and economic productivity. The appearance of resistance against classical drug treatments generates interest in the development of new deworming alternatives. We think that research of new plants species may reveal potential antiparasitic compounds. This review is focused on the use of plants and secondary metabolites against intestinal parasites.We discuss the use of plants in traditional medicine and the use of plant secondary metabolites tried in in vitro and in vivo models when available.